Anthropopaty and its assessment in virtual entities - Analide, César (2004)
The introduction and the natural evaluation of virtual entities presenting human like feelings and behaviours, living in virtual worlds, being based on agents, organizations or other kind of artefacts, has been made, almost exclusively, by an evaluation of such characteristics and assumptions, in terms of a set of quantitative variables. In this paper, it is presented an alternative way to analyse and evaluate an intelligent’s system body of knowledge in terms of its anthropopathic potential, that considers quantitative, qualitative and incomplete information, through and extension to the language of logic programming.